Reincarnation of MSMEs after the Government’s Policy on Economic Recovery Due to the Covid-19 Pandemic in Indonesia - Abdullah, Muh. Ruslan; Fasiha, Fasiha; Arno, Abd. Kadir (Technium Social Sciences Journal, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are experiencing a slump due to the COVID-19 pandemic, and it is feared that it will be challenging to get back up. At this time, the Indonesian government has issued policies through several ministries, including the Ministry of Finance and the Ministry of Health, to stabilize the national economy. Micro, Small, and Medium Enterprises (MSMEs) are the pillars of the national economy, so that this sector needs attention during this pandemic to reincarnate in a better direction. This study aims to find a correlation between government policies and the revival/reincarnation of MSMEs. Data was collected through a questionnaire distributed through the MSME group on Facebook. To find Carried out the relationship between the two variables, the Spearman correlation test. The results found that the level of strength of the relationship or correlation was 0.619, indicating that there was a strong correlation between government policies on the Reincarnation of MSMEs and had a unidirectional relationship that showed a positive value so that the better the government’s alignment with government policies will further improve the state of the Reincarnation of MSMEs towards positive growth.